Continuous degradation of ciprofloxacin in a manganese redox cycling system driven by Pseudomonas putida MnB-1. (November 2018) - Zhou, Nan-Qing; Liu, Dong-Feng; Min, Di; Cheng, Lei; Huang, Xue-Na; Tian, Li-Jiao; Li, Dao-Bo; Yu, Han-Qing
Abstract: Ciprofloxacin (CIP), as an extensively used antibiotic, has been widely detected at a high level in the environment and has raised environmental pollution concerns. Thus, efficient and cost-effective methods for CIP degradation are highly desired. Biologically produced manganese oxides (BioMnOx ) offer a promising perspective for CIP degradation because of their catalytic reactivity and cost-effectiveness. However, the release of Mn(II) from BioMnOx prevents the further oxidation of pollutants. As a consequence, continuous CIP degradation by BioMnOx is not feasible. In this work, a manganese redox cycling system driven by Pseudomonas putida MnB-1 was constructed for continuous degradation of CIP. In such a system CIP was oxidized continuously and rapidly by re-oxidizing the formed Mn(II) to regenerate reactive BioMnOx, which also protected the strain from CIP toxicity. CIP was degraded through N-dealkylation passway. No significant loss of BioMnOx reactivity was observed in three-cycle CIP degradation process, suggesting the stability of this system. An overlooked intracellular BioMnOx, which was involved in CIP degradation, was discovered in P. putida MnB-1. Moreover, the important role of Mn(III) in facilitating CIP removal in this system was also identified. This work provides useful information to better understand the degradation of antibiotic compounds mediated by microbes in environments. Graphical abstract: Image 1 Highlights: A Mn-cycling biosystem was constructed for continuous degradation of CIP. No loss of BioMnOx reactivity was observed in cycling CIP degradation process. An overlooked intracellular BioMnOx involving in CIP degradation was found. This system can be widely used for the biodegradation of other pollutants.